An experimental evaluation of electrical skin conductivity changes in postmortem interval and its assessment for time of death estimation. (1st February 2016) - Cantürk, İsmail and Karabiber, Fethullah and Çelik, Safa and Şahin, M. Feyzi and Yağmur, Fatih and Kara, Sadık
Abstract: In forensic medicine, estimation of the time of death (ToD) is one of the most important and challenging medico-legal problems. Despite the partial accomplishments in ToD estimations to date, the error margin of ToD estimation is still too large. In this study, electrical conductivity changes were experimentally investigated in the postmortem interval in human cases. Electrical conductivity measurements give some promising clues about the postmortem interval. A living human has a natural electrical conductivity; in the postmortem interval, intracellular fluids gradually leak out of cells. These leaked fluids combine with extra-cellular fluids in tissues and since both fluids are electrolytic, intracellular fluids help increase conductivity. Thus, the level of electrical conductivity is expected to increase with increased time after death. In this study, electrical conductivity tests were applied for six hours. The electrical conductivity of the cases exponentially increased during the tested time period, indicating a positive relationship between electrical conductivity and the postmortem interval. Highlights: Estimation of ToD is one of the most critical concepts in forensic medicine. Electrical conductivity changes were investigated in human cases. Electrical conductivity measurements give promising clues about postmortem interval. There is a positive relationship between conductivity and postmortem interval.